H Hubungan Kadar Kolestrol Dalam Darah Dengan Tingkat Nyeri Kepala Pada Penderita Hipertensi di Desa Keramat Kecamatan Martapura Timur - Suwandewi, Alit; Mira, Mira; Daud, Izma; Khalilati, Noor; Aprillia, Hanura; Prisilia, Ni Kadek Neviska (LPPM Universitas Sari Mulia, 2024)
Background: Non-communicable diseases are still a serious problem in Indonesia and the world. One of the non-communicable diseases is hypertension, hypertension occurs due to narrowing of blood vessels due to several factors, one of which is the accumulation of excess cholesterol fat. Hypertension often causes typical symptoms such as headache. Objective: To determine the relationship between blood cholesterol levels and the level of headache in patients with hypertension in Keramat Village, East Martapura District. Methods: The sampling technique used nonprobability sampling with a total sampling method involving 57 respondents with hypertension in Keramat Village, East Martapura District. This study used measurement sheet instruments using the spearman rank analysis test. Results: The study showed that the most respondents' cholesterol levels were in the high limit group (200-239mg/dL) as many as 36 respondents (63.2%) and the most head pain levels were in the moderate pain category (4-6) as many as 26 respondents (45.61%), the spearman rank test analysis showed the results of p-value = 0.000. Conclusion: There is a relationship between blood cholesterol levels and headache levels in hypertensive patients in Keramat Village, East Martapura District.